The Influence of Transactional Political Interests on Corrupt Behavior among Government Officials - Chandra Arie widiyoko; Bambang Martin Baru; Endang Murti; Aries Purwanto (Jurnal Sosial, Politik dan Budaya (SOSPOLBUD), 2026)
Transactional politics is a precursor to corruption involving public officials because it enables those in power to exercise their authority through the selective appointment of bureaucrats to structural positions based on the buying and selling of public offices or political interests. This practice represents a form of money politics that undermines the merit-based system and perpetuates corruption. The buying and selling of public positions occur when government officials pay a certain amount of money to regional leaders or other authorized officials in exchange for strategic positions within the government. This practice has existed for a long time in public administration and is often perceived as a common and acceptable phenomenon. Furthermore, public officials exploit this weakness as a political tool to expand and consolidate their networks of power. Therefore, this study aims to examine the extent to which transactional political interests influence the political behavior of government officials.